2003
DOI: 10.1016/s0741-5214(03)00790-0
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of saphenous nerve injury after greater saphenous vein stripping: prevalence, severity, and relevance for modern practice

Abstract: Signs and symptoms of saphenous nerve injury are common at long-term follow-up after greater saphenous vein stripping to the ankle. However, there appears to be little, if any, significant resultant morbidity. The risk of saphenous nerve injury should therefore not be considered a reason to avoid stripping of the greater saphenous vein to the ankle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 7 publications
(10 reference statements)
5
57
1
9
Order By: Relevance
“…Morrison had declared similar results with transient nerve deficits. The symptoms consistent with nerve injury after complet GSV stripping affected quality of life in only 2.3% at long term evaluation 14 . According to a recently published study, complet GSV stripping showed better nerve injury results (19% at one month) than the nerve injury results of restricted GSV stripping of another study (27% after surgery) 8,17 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Morrison had declared similar results with transient nerve deficits. The symptoms consistent with nerve injury after complet GSV stripping affected quality of life in only 2.3% at long term evaluation 14 . According to a recently published study, complet GSV stripping showed better nerve injury results (19% at one month) than the nerve injury results of restricted GSV stripping of another study (27% after surgery) 8,17 .…”
Section: Discussionmentioning
confidence: 92%
“…Currently, the only way to decrease the need for further operation in varicose veins, is routine stripping 13 . GSV stripping in patients suffering from superficial venous insufficiency ensures clear improvements in the quality of life 8,9,14 . It also should not be forgotten that when the saphenous vein is already displaying varicoses and incompetency, it will be unstable to use it as a graft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu hastaların postoperatif 3.ayda 2 (%40) tanesinde safen sinir hasarı ile ilgili şikayetlerin düzeldiği görüldü. Safen ven striping işleminin kasıktan ayağa doğru yapılmasıyla safen sinir hasarının azaldığını gösteren çalışmalar mevcuttur (3,9). Kliniğimizde striping işlemi kasığa doğru uygulanmaktadır.…”
Section: Tartışma Bulgularunclassified